Effects of polarized and pyramidal training, with or without mindfulness, on race time and performance in amateur runners: Protocol for a randomized controlled trial - Jerman Jesyd Cruz-González; Carlos Alberto Castillo Daza; Luis Alberto Cardozo; Víctor Hugo Arboleda Serna (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Problem: Road races in athletics has increased worldwide in recent years, leading to a growth in amateur runners (AR). Despite this growth, research aimed at this population is scarce and has methodological weaknesses. One topic of recent interest in AR is the effects of training intensity distribution (TID) and mindfulness on race time (RT); however, there is not enough evidence to establish a consensus among scientists, trainers, and athletes. Objective: To compare the effects of four training programs with polarized and pyramidal TID models on 10 km RT, ventilatory thresholds one and two, maximum aerobic speed, maximum oxygen consumption and body composition in AR. Method: A randomized controlled clinical trial with four parallel arms. The study groups include two with a polarized TID model and two with a pyramidal TID model, both combined with and without a mindfulness program over 12 weeks. Mindfulness practice will consist of 65 minutes per week through individual sessions and group workshops. Discussion: The practice of recreational athletics is increasing; however, the effect of TID and mindfulness on RT in this population have not been extensively studied.